COMPARATIVE ASSESSMENT OF EFFECT OF COMBINED DRUGS OF ACE INHIBITOR AND DIURETIC (“NOLIPREL FORTE” AND “CAPOZIDE”) ON CARDIOVASCULAR REMODELING IN HYPERTENSIVE PATIENTS - T. D. Kaplanov; V. V. Ivanenko; N. V. Ryasancevа; A. V. Legkiy; L. P. Anisimova; Yu. M. Lopatin (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To assess antihypertensive efficacy and effect on cardio-vascular remodeling of combined drugs of ACE inhibitor and diuretic, “Noliprel forte” (NF) and “Capozide” (CA), in hypertensive high risk patients.Material and methods. 50 hypertensive (II grade) patients (25 men and 25 women, 19-65 years old) with high cardio-vascular risk took part in comparative opened randomized study. No one of patients received antihypertensive therapy before study. All patients were randomized for therapy with one of combined drug of ACE inhibitors and diuretic. 25 patients took NF (perindopril 4 mg and indapamide 1,25 mg), and 25 patients -CA (captopril 50 mg and hydrochlorothiazide 25 mg). Duration of observation period was 6 months. Before study, after 3 and 6 months of therapy ambulatory blood pressure monitoring (ABPM), echocardiography, cardiac and vessel Dopplerography, ultrasound scanning of general carotid arteries with detection of intima-media thickness (IMT), pulse wave speed (PWS) were held in all patients. Blood bio-chemical analysis was done also.Results. After 3 months 2 patients in NF group and 4 ones in CA group were required to reinforce of ther-apy with additional administration of perindoprile 4 mg and captopril 50 mg respectively. As a result of 6-month of therapy in NF group systolic dlood pressure (BP) decreased in 14,0% (р<0,001) and diastolic BP – на 12,9% (р<0,001). CA reduced systolic BP by 17,9% (р<0,0001) and diastolic BP – by 17,5% (р<0,001). 76% and 70% of patients in NF and CA groups, respectively, reached target BP level. Positive dynamic of daily profile of BP was observed according to ABPM data. Cerebral blood flow did not worsen despite of BP decrease. Both drugs decreased in thickness of inter-ventricular septum and left ventricular mass. Besides, NF decreased in thickness of left ventricular posterior wall. Both drugs reduced in IMT and decreased in PWS. NF therapy did not change of blood biochemical parameters. CA therapy, opposite, resulted in significant growth of plasma uric acid by 39,6%.Conclusion. 6-month therapy with NF showed high antihypertensive efficacy for both of drugs, which did not accompany with cerebral blood flow disturbances. Both drugs also showed an ability for positive effect on cardio-vascular remodeling (with NF priority), improvement of artery wall elasticity. NF, unlike CA, did not increase in plasma uric acid level.